Improving the Caesarean Decision by Robson Classification: A Population-Based Study by 5,323,500 Livebirth Data - H. Omer Tontus; Saniye Nebioglu (Ubiquity Press, 2020)
Background: Caesarean section is a major obstetric intervention for saving lives of women and their newborns from pregnancy- and childbirth-related complications. C-Section rate is considered an important indicator for measuring obstetric services in any country, region, or institution. In many countries, based on population, all-cause C-Section rates have increased steadily during the past half century. The high and rising C-Section rate is certainly a cause for concern, and evidence-based information is needed as to how or why the C-Section rate has increased and what needs to be done. In this study, we tried to demonstrate how the Robson Classification can be used as a common starting point to audit caesarean deliveries. Objectives: Given the lack of a scientifically proven classification system to observe and compare caesarean rates, the WHO proposes adopting the Robson's criteria-related grouping as an internationally applicable C-Section classification system. Methods: We conducted a retrospective study to look into the relation of Robson Criteria and C-Section. Our four years of study encompass 5,323,500 livebirths in Turkey and provide an important source of information for evaluating statistical data. Findings: We analysed pregnancies according to the percentage of live births in Robson's groups and the caesarean rate within the Robson's groups. In total, 2,764,373 pregnant women have undergone caesarean over 4 years with a 51.9% C-Section rate. According to our findings, as time progresses, the R5 group are expanding due to the caesarean sections groups R1-R4. The R5 group C-Section rate increased regularly from 22.2% in 2013 to 24.3% in 2016. Caesarean sections performed in R1-R4 groups cause subsequent pregnancies of these women to result in caesarean section. Conclusions: Our results suggest the Robson classification system will help in analysing, screening, auditing, and comparing caesarean rates across different hospitals, countries, or regions and will help to create and implement effective strategies specifically to reach WHO recommended C-Section rates.